Tumor-associated M2 macrophages promote prostate cancer invasion through the M-CSF-PCLAF pathway - Yitian Ou; Chunwei Ye; Haiyang Jiang; Yong Zhu; Chengxing Xia; Delin Yang (PLoS ONE, 2026)
Background Prostate cancer (PCa), particularly in its advanced and castration-resistant forms, remains a major threat to men’s health, with the tumor microenvironment (TME) playing a crucial role in its progression. Tumor-associated macrophages (TAMs), especially the M2 phenotype, are key components of the TME. Our previous work identified that M2 TAMs in PCa upregulate M-CSF secretion via the MS4A6A-MYC pathway. This study aims to identify the critical downstream effector within PCa cells that mediates the tumor-promoting effects of M-CSF. Methods The impact of M-CSF on PCa cell (PC3 line) viability, invasion, and migration was assessed using CCK-8, Transwell, and wound healing assays. To identify M-CSF-regulated downstream proteins, a comprehensive proteomic analysis (DIA-PASEF) was performed on PC3 cells treated with or without M-CSF. Bioinformatic analyses screened for differentially expressed proteins. Key candidate PCLAF was further validated using Western blot, analysis of TCGA-PRAD data, and immunohistochemistry on a prostate tissue microarray (79 patients). The functional role of PCLAF was confirmed through in vitro experiments and an in vivo xenograft model in nude mice, comparing tumors from PC3 control cells, PC3 cells overexpressing KIAA0101/PCLAF (PC3-KIAA0101+), and PC3 cells with local M-CSF injections. Results M-CSF stimulation significantly enhanced PC3 cell viability, invasion, and migration in a concentration-dependent manner. Proteomic analysis revealed 95 differentially expressed proteins following M-CSF treatment. Among the top candidates, PCLAF/KIAA0101 was the only protein consistently and significantly upregulated by M-CSF in validation experiments. Analysis of TCGA data confirmed PCLAF’s significant overexpression in PCa tumors and its association with poorer disease-free survival. Tissue microarray analysis demonstrated that PCLAF expression was significantly higher in PCa tissues compared to benign tissues and positively correlated with higher Gleason Grade Groups and ISUP risk groups. In the xenograft model, both PC3-KIAA0101+ and PC3 + M-CSF groups exhibited significantly increased tumor growth, volume, and weight compared to the control group. IHC, Western blot, and PCR analyses of the xenograft tumors confirmed that PCLAF expression levels followed the pattern: PC3-KIAA0101+ > PC3 + M-CSF > control, and were positively correlated with tumor growth. Conclusions This study indicates that M-CSF, secreted by M2 TAMs, promotes prostate cancer progression by upregulating the expression of PCLAF/KIAA0101 in cancer cells. PCLAF is overexpressed in PCa, correlates with tumor malignancy and poor prognosis, and its upregulation is sufficient to enhance tumor growth in vivo. These findings indicate the M-CSF-PCLAF axis as a key mechanism through which TAMs drive PCa invasion and progression, identifying PCLAF as a potential therapeutic target.